Foundations of Spirituality : The Human and the Holy; A Systematic Approach - Streeter, Carla Mae (Book collections on Project MUSE., 2012)
Scholarly approaches to spirituality often overlook the need for a sound anthropology as the base for explaining conversion, the dynamic of grace, and the effects of conversion in virtue theory. In Foundations of Spirituality, longtime educator Carla Mae Streeter provides a more adequate account of what it means to be a person before God. By mining the insights of Bernard Lonergan on human consciousness and the virtue theory of Thomas Aquinas, she presents a clear and integrated incarnational spirituality. Streeter argues that God works with precisely what God has made, enhancing it rather than overriding or disposing of it. The basic premise of this book is that every person is called to holiness, which comes about through the relationship of the human with the Divine. It is a divine summons heard and responded to by a human being. --